2017
DOI: 10.3390/ijms18081794
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective and Nerve Regenerative Approaches for Treatment of Erectile Dysfunction after Cavernous Nerve Injury

Abstract: Erectile dysfunction (ED) is a significant cause of reduced quality of life in men and their partners. Cavernous nerve injury (CNI) during pelvic surgery results in ED in greater than 50% of patients, regardless of additional patient factors. ED related to CNI is difficult to treat and typically poorly responsive to first- and second-line therapeutic options. Recently, a significant amount of research has been devoted to exploring neuroprotective and neuroregenerative approaches to salvage erectile function in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 128 publications
(161 reference statements)
0
24
0
Order By: Relevance
“…Cavernous injury, diabetes, and other types of ED-associated disorders are not significant for first-line clinical treatment with PDE5i, so more treatment regimens and means are needed for Ed treatment [25]. At present, the relationship between RhoA/ROCK signaling and ED has attracted the attention of many researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Cavernous injury, diabetes, and other types of ED-associated disorders are not significant for first-line clinical treatment with PDE5i, so more treatment regimens and means are needed for Ed treatment [25]. At present, the relationship between RhoA/ROCK signaling and ED has attracted the attention of many researchers.…”
Section: Discussionmentioning
confidence: 99%
“…As it pertains to ED, PRP has been found to contain growth factors such as vascular endothelial growth factor (VEGF), plateletderived growth factor (PDGF), epidermal growth factor (EGF), insulin-like growth factor (IGF), and fibroblast growth factor (FGF) (18,19). Many of these growth factors have been shown to have a role in improving erectile function in both preclinical and clinical studies (20). Specifically, animal studies injected with VEGF and using a cavernous nerve injury (CNI) model of ED have shown greater salvage of erectile function compared to controls (21).…”
Section: Platelet-rich Plasma (Prp)mentioning
confidence: 99%
“…There is a lack of understanding as to whether PRP can play a neuroprotective or nerve regeneration role in salvaging erectile function after CNI, and additional studies comparing early versus delayed administration would be beneficial (20). Currently, the Mayo Clinic (Rochester, MN, USA) is recruiting patients for a clinical trial that involves the application of autologous PRP circumferentially around the neurovascular bundle during a radical prostatectomy as a neuroprotective mechanism (https://clinicaltrials.gov/ct2/ show/NCT02957149) (12).…”
Section: Platelet-rich Plasma (Prp)mentioning
confidence: 99%
See 1 more Smart Citation
“…Prostate cancer is the second leading cause of cancer-related death in men worldwide [1, 2]. Erectile dysfunction (ED) administered by injury of cavernous nerve is a significant problem following prostate cancer surgery, which seriously affects the quality of life of patients [35]. Adipose tissue-derived stem cells (ADSCs) has significant treatment effect for ED in diabetics, post-prostatectomy patients, and those with peyronie’s disease [6, 7].…”
Section: Introductionmentioning
confidence: 99%